BARA’AN TRADITION (STUDY ON THREE VILLAGES IN MAINTAINING BARA’ANTRADITION AT KECAMATAN BANTAN KABUPATEN BENGKALIS) - Rara Ramadhani; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at Kecamatan Bantan Kabupaten Bengkalis. The purpose of this research is to know the effort of society to maintain the continuity of Bara'an tradition at Kecamatan Bantan Kabupaten Bengkalis. The purpose of this research is to know the effort of society to maintain. The focus of this research is the essence of Bara'an tradition implementation by society at Kecamatan Bantan Kabupaten Bengkalis. The technique of determining samples in a purposive sampling and set the number of samples as many as 8 people. The author uses qualitative descriptive method and Instrument data is observation, interview and documentation. Research conducted, the authors found that there are two great essence of bara'an tradition that is the relationship and cultural life. Research conducted found that the timing of bara'an tradition is after completing solat idul fitri, Bara’an done for the longest for a week and the fastest for four days. the series of bara’an implementation starts from the gathering of the community in the mosques every village after the solat idul fitri, then the community will jointly crush first house that will be addressed in Bara’an, after determined which house will be addressed first then the head of the entourage will turn on siren mark Bara’an begins, then the entourage will move to the first house and so on. When they reach the targeted house, the community will be led to read prayers and sholawat. After that will be served a variety of Eid foods such as wet and dry sponge cake variety, various crackers, durian leaf, vegetable lontong, ketupat and various other meals. After eating the dish served by the owner of the house then the group will leave and go to the next house. Efforts made to maintain the existence of bara'an in Bantan District is, Growing Enthusiasm Community Participation, Not Limiting Membership Bara'an Tradition, and Cooperation Government in Keeping the Meaning of Bara'an. Keywords: Tradition, Bara'an, Essence, Effort